Pelaksanaan Supervisi Klinis Peningkatan Keterampilan Guru SMK Negeri 1 Tuban dalam Menggunakan Model Blended Learning Sebagai Upaya Mengefektifkan Pembelajaran pada Masa Pandemi Covid 19 - Subandi, Subandi (FKIP Unirow Tuban, 2022)
In the first cycle, there were as many as 24 teachers (80% teachers) at SMK Negeri 1 Tuban managed to achieve the minimum completeness of the performance test using the Blended learning model. While the average value in the first cycle reached 79.69. In the second cycle, all teachers (100% teachers) at SMK Negeri 1 Tuban managed to achieve the minimum completeness of the performance test using the Blended learning model, with the average score in the second cycle reaching 87.42. The indicator of success in the performance test is the number of teachers who get the